Medical confidentiality against disclosure in the public interest: should such protective privilege ends when public peril begins? - Jahn Kassim, Puteri Nemie (LexisNexis Malaysia Sdn Bhd, 2006)
The integrity of the doctor-patient relationship is based on safeguarding patient's confidential information. Medical ethics stress the importance of confidentiality based on the assumption of an individual's right to privacy and on the assumption that the consequences of breaching this right to privacy normally outweigh possible benefits. As stated in the Hippocratic Oath, 'All that may come to my knowledge in the exercise of my profession ... I will keep secret and never reveal.' However, the duty of confidentiality is by no means an absolute concept. The patient's interest in his privacy must be balanced with other potentially conflicting interests. In providing care, medical professionals often find themselves trapped between conflicting duties and obligations.